(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to investigate the stress stages of performance athletes in the context of Paraná sports. Specifically, it was compared the stress between the genders and what symptoms of stress prevalent in athletes. The subjects were 238 athletes, 110 (46%) were male and 128 (54%) female. As an instrument for data collection used the Inventory of Stress Symptoms for Adults (ISSL), aimed at identifying the points of stress. The data collection was individual in JAP’S 2008. Data were analyzed using descriptive statistics, with evaluation of data normality using the Shapiro Wilk test, and characterization of categorical data, absolute and relative frequency. To verify the association was used Qui Square and Qui Square 2X3 2X2 with Yates correction adopting P <0.05. Most evaluated athletes who presented stress were in the phase of resistance (95.25%). The percentage variation between the genders was not significant (p = 0.28). It was found that the symptoms of psychological/ physical stress more prevalent were the psychological (61%) against the physical (39%). Thus, it is possible to conclude that the phases and the stress symptoms is presented as an intervening factor in motor performance of performance athletes.